Seismic Safety of Rockfill Dam with Asphalt Concrete Core on Overburden Layer - FENG Rui; LI Yuqi; SHI Wenjie (Renmin Zhujiang)
As the rockfill dam with an asphalt concrete core is built over the thick overburden layer,the overburden layer affects the dynamic response of the dam and aggravates the whiplash effect.Cutoff structures are also affected,especially the cutoff wall of the dam base and the asphalt concrete core of the dam,which are thin and prone to crack during an earthquake,and hence,they are the weak links of engineering.In the case of a rockfill dam with an asphalt concrete core,its height is 85.5 m,and the cutoff wall of the dam base has a depth of 110 m.To explore the seismic safety of the dam and its cutoff system,this study employs the sub-modeling technique to analyze the seismic time history of the cutoff wall and the core on the basis of static analysis.The results indicate that the seismic effect greatly influences the top and bank slope of the core and both sides of the cutoff wall,and the range and value of tensile stress increase to a great extent.It is suggested that corresponding measures should be taken to reinforce local regions.